2008
DOI: 10.1080/09735070.2008.11886323
|View full text |Cite
|
Sign up to set email alerts
|

Breast Feeding Practices among the Hakkipikkis: A Tribal Population of Mysore District, Karnataka

Abstract: The practice of breast-feeding is almost universal. In the present study, an attempt was made to understand various aspects of feeding practices among the Hakkipikkis of Mysore district of Karnataka state. One hundred and twenty five (125) mothers were interviewed personally on breast feeding practices such as Initiation of Breast-feeding, Duration of Breast feeding, Introduction of pre-lacteal feed and Supplementary feeding practices etc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 2 publications
1
24
1
Order By: Relevance
“…These PLFs were also reported in Philippines [28]. However, in India and Bangladesh the common feeds were honey, herbs, sugar water, gripe water, and cow's milk [34, 35, 37, 40–42]. This variation in the type of PLF between different countries could be attributed to the difference in culture, local beliefs, and availability of different feeds.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…These PLFs were also reported in Philippines [28]. However, in India and Bangladesh the common feeds were honey, herbs, sugar water, gripe water, and cow's milk [34, 35, 37, 40–42]. This variation in the type of PLF between different countries could be attributed to the difference in culture, local beliefs, and availability of different feeds.…”
Section: Discussionmentioning
confidence: 55%
“…Their reasons were perceived milk insufficiency, prevention of dehydration, hypoglycemia, and neonatal jaundice, and well as cleansing the baby's gut and rest the mother [5]. Indian studies reported that PLFs were given to clean infants systems [40], being traditional belief as they considered colostrum thick, cheesy, indigestible, unhygienic, and not good for the baby [35]. In Bangladesh, tradition, child becoming normal and quiet, delayed milk suction, and clearing newborn's oral cavity were the most cited reasons for giving PLFs [42].…”
Section: Discussionmentioning
confidence: 99%
“…The breastfeeding rates among tribal and indigenous population have been noted to be lower than the national average by different authors. [11][12][13] The districts of northern part of West Bengal are characterized by a higher proportion of scheduled tribes.…”
Section: Introductionmentioning
confidence: 99%
“…16 Dakshayani et al, in Mysore, study done among Hakkipikkis tribal population, 40% of them gave pre lacteals. 17 In a study done by Surva Pathi et al, in rural area of Orissa, 56.4% of babies had received pre-lacteal feeds. 18 Less number of infants received pre-lacteals in Chandrasekhar et al, study (15.2%) done in Nepal.…”
Section: Discussionmentioning
confidence: 99%